Notes on the Morphology and Biology of Syneura cocciphila (Diptera: Phoridae). Issue 1 (20th January 2018) - Muñoz, Keily; Manrique, Marilyn B; Sotelo-Cardona, Paola; Gaimari, Stephen D; Kondo, Takumasa
Abstract: Herein we provide information on the morphology and duration of the different stages of development of Syneura cocciphila (Coquillett; Diptera: Phoridae), a phorid-fly predator of the Colombian fluted scale Crypticerya multicicatrices Kondo and Unruh (Hemiptera: Monophlebidae). The time from oviposition to adult emergence was 20.04 d. The duration of the different growth stages was as follows: egg 1.38 (±0.18) d; three larval stages combined 4.5 (±0.19) d; prepupa 1.63 (±0.09) d; and pupa 12.53 (±0.12) d. On average, adult females lived 13.23 (±0.77) d and adult males lived 11.13 (±0.61) d under laboratory conditions. S. cocciphila is a common species in the city of Cali, department of Valle del Cauca, Colombia, and is an effective biological control agent of the scale insect pest C. multicicatrices . This is the first detailed study on the biology of S. cocciphila .